2004
DOI: 10.2172/910959
|View full text |Cite
|
Sign up to set email alerts
|

Initial Scaling Studies and Conceptual Thermal Fluids Experiments for the Prismatic NGNP Point Design

Abstract: Table of contents iii Nomenclature iv Heated flow experiments Vertical tube Lower plenum Fluid dynamics experiments for lower plenum Concluding remarks References cited Bo* Jackson buoyancy parameter, Gr* / (Re Dh 3.425 Pr 0.8) d + wire diameter, d u / f, f friction factor, 2 b g c w / G 2 Gr* Grashof number based on heat flux, g q" wall D h 4 / (k 2) K v acceleration parameter, (b / V b 2) (dV b / dx) v Nu Nusselt number, h D h / k b Pr Prandtl number, c p /k q + heat flux, q" wall / (G c p) Re Reynolds numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 102 publications
(111 reference statements)
0
2
0
Order By: Relevance
“…The PIRT was a preliminary characterization of important system behavior during PCC and DCC scenarios. A study by McEligot and McCreery, 2004, identified important thermal hydraulic phenomena during normal operation and the PCC scenario for a prismatic core design. Important thermal hydraulic phenomena (including DCC phenomena) are shown schematically in Figure 4.…”
Section: Iv1 Vhtr Thermal Hydraulics Researchmentioning
confidence: 99%
“…The PIRT was a preliminary characterization of important system behavior during PCC and DCC scenarios. A study by McEligot and McCreery, 2004, identified important thermal hydraulic phenomena during normal operation and the PCC scenario for a prismatic core design. Important thermal hydraulic phenomena (including DCC phenomena) are shown schematically in Figure 4.…”
Section: Iv1 Vhtr Thermal Hydraulics Researchmentioning
confidence: 99%
“…The Very High Temperature Reactor (VHTR) is the leading candidate for the Next Generation Nuclear 1996] is assumed in this study. VHTR vessel thermalhydraulic phenomena that are of importance during normal, reduced power, and accident operation were identified by McEligot and McCreery, 2004, and are indicated in Figure 1. The objectives of the experiments are, 1), provide benchmark data for assessment and improvement of codes proposed for NGNP designs and safety studies, and, 2), obtain a better understanding of related phenomena, behavior and needs.…”
Section: Introductionmentioning
confidence: 99%